The antimicrobial peptide MK58911-NH2 acts on planktonic, biofilm, and intramacrophage cells of cryptococcus neoformans - de Lacorte Singulani, Junya [UNESP]; Oliveira, Lariane Teodoro [UNESP]; Ramos, Marina Dorisse [UNESP]; Fregonezi, Nathália Ferreira [UNESP]; Gomes, Paulo César [UNESP]; Galeane, Mariana Cristina [UNESP]; Palma, Mario Sergio [UNESP]; Fusco Almeida, Ana Marisa [UNESP]; Mendes Giannini, Maria José Soares [UNESP] (American Society for Microbiology, 2021)
Cryptococcosis is associated with high rates of morbidity and mortality, especially in AIDS patients. Its treatment is carried out by combining amphotericin B and azoles or flucytosine, which causes unavoidable toxicity issues in the host. Thus, the urgency in obtaining new antifungals drives the search for antimicrobial peptides (AMPs). This study aimed to extend the understanding of the mechanism of action of an AMP analog from wasp peptide toxins, MK58911-NH2, on Cryptococcus neoformans. We also evaluated if MK58911-NH2 can act on cryptococcal cells in macrophages, biofilms, and an immersion zebrafish model of infection. Finally, we investigated the structure-antifungal action and the toxicity relationship of MK58911-NH2 fragments and a derivative of this peptide (MH58911-NH2). The results demonstrated that MK58911-NH2 did not alter the fluorescence intensity of the cell wall-binding dye calcofluor white or the capsule-binding dye 18b7 antibody-fluorescein isothiocyanate (FITC) in C. neoformans but rather reduced the number and size of fungal cells. This activity reduced the fungal burden of C. neoformans in both macrophages and zebrafish embryos as well as within biofilms. Three fragments of the MK58911-NH2 peptide showed no activity against Cryptococcus and not toxicity in lung cells. The derivative peptide MH58911-NH2, in which the lysine residues of MK58911-NH2 were replaced by histidines, reduced the activity against extracellular and intracellular C. neoformans. On the other hand, it was active against biofilms and showed reduced toxicity. In summary, these results showed that peptide MK58911-NH2 could be a promising agent against cryptococcosis. This work also opens a perspective for the verification of the antifungal activity of other derivatives.
Keywords: Antifungal activity; Antifungal agents; Antimicrobial peptide; Biofilm; Cryptococcosis; Cryptococcus neoformans; Intramacrophage activity; Mechanisms of action; Nonconventional animal models; Systemic fungi; Systemic mycoses